δD values of biomarkers in Hala Hu sediment core H11 - Aichner, Bernhard; Callegaro, Alice; van der Meer, Marcel T J; Wünnemann, Bernd; Yan, Dada; Zhang, Yongzhan; Barbante, Carlo; Sachse, Dirk (In: Aichner, B et al. (2021): Concentrations and δD values of biomarkers in sediment cores H7 and H11 from Hala Hu, China [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.933814, 2021)
Hydrogen isotope composition of aquatic (mid-chain n-alkenes, C20-HBIs, C37-alkenones) and terrestrial (long-chain n-alkanes) biomarker groups were analysed in core H11 from Hala Hu, China. The lake is located on the northern margin of the Tibetan Plateau (97.24 - 97.47°E, 38.12 - 38.25°N, 4078 m above sea level), along the modern marginal zone between the Asian Summer Monsoon (ASM) and westerlies influences. The core was drilled at the deepest point (65 m) of the lake and extends from 0 to 212 cm sediment depth. According to the age-model (Yan et al., 2020) the covered time period is modern - 9216 cal yr BP. For separate δD-analysis of n-alkanes and n-alkenes, after quantification the non-polar aliphatic fraction was further split chromatographically into a saturated and unsaturated fraction, using aluminum-coated silicagel as stationary phase and hexane and DCM as solvents. Compound specific hydrogen isotope values were then obtained by using gas chromatography isotope ratio mass spectrometry (GC-IRMS). We used a Thermo Scientific® Trace GC equipped with a Restek RTX-5 column (30 m, inner diameter 0.25 mm, film thickness 0.25 μm). The GC was connected via a GC Isolink with high temperature combustion furnace (1400 °C) and a Conflo IV interface to a Delta V Plus isotope ratio mass spectrometer. The δD values of the alkenones were determined by a GC/Thermal Conversion/isotope ratio monitoring mass spectrometer (GC-TC-irMS). For this a GC, equipped with a CPsil 5 CB column (25 meters, 0.32 mm inner diameter, film thickness 0.4 μm) was coupled to a GC-isolink I via a Conflo IV to a Thermo Electron DELTA V mass spectrometer.
Keywords: Alkenone; Biomarker; China; highly branched isoprenoid (HBI); isotopes; n-alkane; n-alkene; Paleoclimate; Sediment core; Tibetan Plateau